2023
DOI: 10.1002/iid3.789
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: METTL3 enhances the effect of YTHDF1 on NEDD1 mRNA stability by m6A modification in diffuse large B‐cell lymphoma cells

Abstract: Aim Diffuse large B‐cell lymphoma (DLBCL) remains the most frequent subpopulation of lymphoma, and N6‐methyladenosine (m6A) was implicated in the DLBCL progression. Herein, we sought to decipher the m6A‐asociated mechanism of NEDD1 in DLBCL development. Methods The NEDD1 expression profile in DLBCL was assessed by quantitative real‐time polymerase chain reaction (RT‐qPCR) and Western blot. NEDD1 was artificially downregulated or upregulated in DLBCL cells, followed by EdU, Transwell assays and flow cytometry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…M 6 A methylation plays a vital role in tumorigenesis, tumor progression, and immunotherapy. As a typical reader for m 6 A methylation, METTL3 and the levels of m 6 A-modified mRNA are up-regulated in many types of cancer cells and tumor tissues [ 29 , 30 ]. M 6 A levels and METTL3 expression in DLBCL cell lines and DLBCL tissues were higher than those in human B lymphocytes and control inflammatory lymph glands, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M 6 A methylation plays a vital role in tumorigenesis, tumor progression, and immunotherapy. As a typical reader for m 6 A methylation, METTL3 and the levels of m 6 A-modified mRNA are up-regulated in many types of cancer cells and tumor tissues [ 29 , 30 ]. M 6 A levels and METTL3 expression in DLBCL cell lines and DLBCL tissues were higher than those in human B lymphocytes and control inflammatory lymph glands, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, silencing of METTL3 inhibited the proliferation of DLBCL cells [ 31 ]. Feng et al [ 30 ] reported that interference with METTL3 led to decreases in NEDD1 mRNA expression and m 6 A methylation levels in DLBCL cells. In natural killer/T-cell lymphoma (NKTCL), a type of non-Hodgkin’s lymphoma, METTL3 was up-regulated when compared to its expression in normal NK cells.…”
Section: Discussionmentioning
confidence: 99%